Delayed Care Seeking and Outcomes of Testicular Torsion among Children during the COVID-19 Pandemic: A Systematic Review and Meta-Analysis - Ye, Zihan; Chen, Hongsong; Liu, Xing; Wei, Guanghui (European Journal of Pediatric Surgery, 2022)
Introduction Since the onset of coronavirus disease 2019 (COVID-19), stay-at-home orders and fear caused by the pandemic have had a significant effect on the timing and outcomes of testicular torsion. However, the evidence was limited since the study results were inconsistent. This study aims to examine the hospitalization rates, timing, and outcomes of testicular torsion in children before and during the pandemic.Materials and Methods Using PubMed, Embase, and Google Scholar databases, we conducted a systematic search and meta-analysis of studies reporting the timing and outcomes of children admitted with testicular torsion before and during the COVID-19 pandemic. Subgroup analyses were conducted to explore possible sources of heterogeneity.Result The outcomes of 899 testicular torsion patients from eight studies were evaluated. Our study found an increased hospitalization rate for patients with testicular torsion (incidence rate ratio = 1.60, 95% confidence interval [CI]: 1.27–2.03; p = 0.001). Despite a significant increase in the duration of symptoms during the COVID-19 pandemic (weighted mean difference = 11.04, 95% CI: 2.75–19.33; p = 0.009), orchiectomy rates did not increase (odds ratio = 1.33, 95% CI: 0.85–2.10; p = 0.147).Conclusion During the COVID-19 pandemic, hospitalization rates for testicular torsion and the duration of symptoms among children increased significantly. Moreover, the rate of orchiectomy did not increase during the pandemic, indicating that pediatric emergency services have remained efficient and have prevented an increase in the number of orchiectomies performed despite pandemic-related closures and delays in transporting patients to medical care.
Keywords: testicular torsion; pediatric emergency; COVID-19; orchiectomy